ANALISIS PERAN BUNG TOMO DALAM PERTEMPURAN 10 NOVEMBER 1945 DI SURABAYA - Robani, Robani (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This article discusses the November 10 battle in Surabaya. The purpose of this research is to find the history and mobilization of the battle in Surabaya and the values of nationalism contained therein. The method used in this paper uses historical methods with qualitative research using a descriptive approach. The sources used in this paper are historical sources that use historical analysis techniques that use interpretations of historical facts which include books, documents and journals related to the November 10 battle in Surabaya. The results of this study indicate that the battle for Surabaya on November 10 was motivated by the Yamato hotel incident where soldiers tried to fly the Dutch flag, causing anger among the people and youth of Surabaya. The battle in Surabaya was not only carried out armed, but also carried out through political and diplomatic channels. The mobilization that took place in the Battle of Surabaya was a spirit of unity shown by a group with other groups even though the underlying spirit was different. The value of nationalism contained in this paper is the persistence and high loyalty of the Indonesian people and Surabaya youth to uphold and fight for Indonesian independence.